Efficacy of RNA interference knockdown using aerosolized short interfering RNAs bound to nanoparticles in three diverse aphid species. Issue 3 (17th March 2017) - Thairu, M. W.; Skidmore, I. H.; Bansal, R.; Nováková, E.; Hansen, T. E.; Li‐Byarlay, H.; Wickline, S. A.; Hansen, A. K.
Abstract: RNA interference (RNAi) has emerged as a promising method for validating gene function; however, its utility in nonmodel insects has proven problematic, with delivery methods being one of the main obstacles. This study investigates a novel method of RNAi delivery in aphids, the aerosolization of short interfering RNA (siRNA)–nanoparticle complexes. By using nanoparticles as a siRNA carrier, the likelihood of cellular uptake is increased, when compared to methods previously used in insects. To determine the efficacy of this RNAi delivery system, siRNAs were aerosolized with and without nanoparticles in three aphid species : Acyrthosiphon pisum, Aphis glycines and Schizaphis graminum . The genes targeted for knockdown were carotene dehydrogenase ( tor ), which is important for pigmentation in Ac. pisum, and branched chain‐amino acid transaminase ( bcat ), which is essential in the metabolism of branched‐chain amino acids in all three aphid species. Overall, we observed modest gene knockdown of tor in Ac. pisum and moderate gene knockdown of bcat in Ap. glycines along with its associated phenotype. We also determined that the nanoparticle emulsion significantly increased the efficacy of gene knockdown. Overall, these results suggest that the aerosolized siRNA–nanoparticle delivery method is a promising new high‐throughput and non‐invasive RNAi delivery method in some aphid species.